The Role of Electronic Marketing in Encouraging Clean Products in the Context of Sustainable Development - imane , Gherzouli; Rabeh, Hamida (Journal of Ecohumanism, 2025)
This research explores the role of digital marketing in raising awareness about clean products as an effective tool within the framework of sustainable development. Clean products are gaining increasing importance in the global market due to the negative environmental impacts of traditional products. The aim of this study is to investigate how modern digital tools—such as social media platforms and digital advertising—can be utilized to promote sustainable products. By examining the case study of Patagonia, the research analyzes digital marketing strategies that have contributed to enhancing consumer awareness of sustainability. The findings show that digital marketing can be a powerful driver of behavioral change, encouraging the widespread adoption of sustainable practices. The paper recommends expanding the use of these strategies across various sectors to achieve the goals of sustainable development.